Remote Afterloading Technology: A Short Review - Siti Amira Othman (Research and Innovation in Technical and Vocational Education and Training, 2023)
Afterloading is a medical technique used in radiation oncology in which catheters with or without applicators are placed inside the patient’s body during the surgery. Respective radioactive sources are also loaded into the patient for treatment.There are remote afterloading of low-dose-rate (LDR), medium-dose-rate (MDR), and high-dose-rate (HDR) radioactive materials for brachytherapy is increasingly performed. This review presents the importance of remote afterloading technology discovery that successfully benefits todays radiation therapy and treatment. Remote afterloading offers great advantages such as improves radiation control, provides technical advantages. The choice of a particular remote afterloading device depends on a few important perspectives such as patients population. Despite any type of remote afterloader, radiation control procedures is vital as much as manual afterloading technology. To reduce patient suffering, shorten hospital stays, and remove radiation risks to medical staff, the first remote afterloading technique was introduced in 1964. It included transferring tiny, highly active cobalt sources back and forth. Although this remote afterloading is an improvement over the manual, radiation risks are still present. Therefore, the remote afterloading machine’s safety design was developed to lower the radiation threats.